2014
DOI: 10.1111/dgd.12117
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial inhibitor sodium azide inhibits the reorganization of mitochondria‐rich cytoplasm and the establishment of the anteroposterior axis in ascidian embryo

Abstract: In ascidian eggs, cytoplasmic and cortical reorganization, previously called ooplasmic segregation, occurs in two phases during the first cell cycle. In the second phase of reorganization, the mitochondria-rich cytoplasm (myoplasm) moves to the future posterior side, concurrent with sperm aster migration along the egg cortex. Although this reorganization is the critical step for establishing the anteroposterior axis, its molecular mechanism is not fully understood. In this study, we showed that low concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 62 publications
2
22
0
Order By: Relevance
“…Previously, we reported that NaN 3 treatment during the second phase of reorganization disturbed cortical tubulin accumulation but not astral microtubule structure (Ishii et al . ), suggesting a specific inhibition of CAMP formation. So we visualized the effects of NaN 3 on the CAMP formation by immunostaining using G1T0 (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Previously, we reported that NaN 3 treatment during the second phase of reorganization disturbed cortical tubulin accumulation but not astral microtubule structure (Ishii et al . ), suggesting a specific inhibition of CAMP formation. So we visualized the effects of NaN 3 on the CAMP formation by immunostaining using G1T0 (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…; Ishii et al . ). In contrast, when the specimens were treated with G1T0, we observed thick microtubule bundles positioned in parallel arrays to the mid‐plane arc (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations